OKLAHOMA BANK BEHAVIOR AND THE PANIC OF 1907 - Loren Gatch (Essays in Economic and Business History, 2010)
While the Panic of 1907 began in New York City, its effects reverberated throughout the United States. This article examines the response of Oklahoma banks to the nationwide restriction of payments beginning in late October of that year. Despite the widespread support of local communities for their banks, Oklahoma institutions cut back on loans and built up their reserves to a greater degree than did country banks nationwide. Of particular concern for Oklahomans in late 1907 was the financing of the cotton crop. Balance sheet evidence suggests that Oklahoma banks in cotton-growing areas reacted more defensively than did banks in wheat-growing areas, where the harvest had already been completed. A multiple regression model exploring changes in Oklahoma bank reserves before and after the Panic not only confirms the relevance of cotton as a factor but also points to bank size, the use of cash substitutes, and political jurisdiction as variables that influenced the extent to which Oklahoma banks increased their reserves in response to the Panic.